Population Study of Endemic Java Palm Pinanga javana in Mount Ungaran, Semarang, Central Java, Indonesia - Rizmoon Nurul Zulkarnaen; Hendra Helmanto; Wihermanto Wihermanto; Enggal Primananda; Iyan Robiansyah; Yayan Wahyu Candra Kusuma (Biosaintifika: Journal of Biology & Biology Education, 2022)
The discovery of Pinaga javana Blume in Mount Ungaran is new information for the distribution of this palm because there was no record of this palm on Mount Ungaran. Therefore, to reveal the population of P. javana in Mount Ungaran, this research was carried out to determine the population structure and habitat preference of P. javana. The study for P. javana was conducted using the focused survey method to explore all the side of Mount Ungaran (northern, southern, western, and eastern). The total area explored is 13 locations. All palm individuals have been recorded for diameter, height, and habitat. The results showed that from 13 locations, the population of P. javana was only found in 5 locations. Mainly on the southern side of Mount Ungaran. The total population of P. javana is around 213 individuals. The highest number of individuals is in the seedlings stage. The population of P. javana found is mostly on steep slopes compared to ridges that tend to be flat. In addition, the suspected habitat as a specific preference is the position of the slopes that are closer to the water source (river). The study also found that the distribution of P. javana was assisted by a dispersal agent (forest civet). In general, this study provides new information for the distribution records of P. javana in Java. Therefore, in this palm conservation function, special efforts are needed to increase the population of P. javana on Mount Ungaran.